Foreign language reading anxiety: Exploring the experiences of EFL students at a state university in Padang, Indonesia - Fitrawati; Insan Kamil; David D Perrodin (English Language Teaching Educational Journal, 2023)
This study investigates the levels of foreign language reading anxiety among EFL students at a state university in Padang, West Sumatra, Indonesia, to identify the main factors contributing to this anxiety. The study included 30 participants who provided data through two questionnaires. The first questionnaire utilized the Foreign Language Reading Anxiety Scale (FLRAS) to assess anxiety levels, while the second questionnaire aimed to determine the primary factor behind this anxiety. The results indicated that 67% of the students experienced moderate anxiety, 20% experienced high levels, and 13% reported low anxiety. The study identified two main factors influencing foreign language reading anxiety: text features and personal factors. Text features encompassed unfamiliar vocabulary, topics, and culture, while personal factors included concerns about the effect of reading and fear of making errors. The second questionnaire revealed that unfamiliar language ranked as the most dominant factor, followed by concerns about the impact of reading, unfamiliar topics, fear of making errors, and unfamiliar culture. Recognizing that reading anxiety is a common experience among language learners is essential. However, with the proper support and guidance, students can overcome these challenges and succeed in their English language learning journey.